1999
DOI: 10.1016/s0002-9440(10)65406-5
|View full text |Cite
|
Sign up to set email alerts
|

CD44 and β1 Integrin Mediate Ovarian Carcinoma Cell Adhesion to Peritoneal Mesothelial Cells

Abstract: Epithelial cancer of the ovary spreads by implantation of tumor cells onto the mesothelial cells lining the peritoneal cavity. The aim of this study was to identify the adhesion molecules involved in the interaction of ovarian carcinoma cells with mesothelial cells. The human ovarian carcinoma cell lines SKOV3 and NIH:OVCAR5 as well as LP9 cells, a human peritoneal mesothelial cell line, were analyzed by flow cytometry for the expression of CD44 and the beta1 integrin subunit. An in vitro adhesion assay was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
172
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(177 citation statements)
references
References 30 publications
3
172
2
Order By: Relevance
“…Contrary to these findings, in human mesothelial cells we have demonstrated that tumourmesothelial adhesion is required for the induction of apoptosis, which cannot be reproduced by the substitution of tumourconditioned media. This is supported by other in vitro work that has implicated cell adhesion molecules, such as CD44 and the b1 integrins, in tumour-mesothelial invasion, (Schlaeppi et al, 1997;Lessen et al, 1999;Strobel and Cannistra, 1999). The requirement for cell -cell contact to initiate the invasive process supports the role of cell membrane bound ligands, such as FasL, as the mediators of mesothelial apoptosis.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Contrary to these findings, in human mesothelial cells we have demonstrated that tumourmesothelial adhesion is required for the induction of apoptosis, which cannot be reproduced by the substitution of tumourconditioned media. This is supported by other in vitro work that has implicated cell adhesion molecules, such as CD44 and the b1 integrins, in tumour-mesothelial invasion, (Schlaeppi et al, 1997;Lessen et al, 1999;Strobel and Cannistra, 1999). The requirement for cell -cell contact to initiate the invasive process supports the role of cell membrane bound ligands, such as FasL, as the mediators of mesothelial apoptosis.…”
Section: Discussionsupporting
confidence: 55%
“…It is well documented that tumour cells adhere rapidly to the mesothelium both in vivo and in vitro, and a role for the cell adhesion molecule CD44 and the integrins b1, a2, a3 and a5 in mesothelial invasion has been postulated (Kiyasu et al, 1981;Schlaeppi et al, 1997;Lessen et al, 1999;Strobel and Cannistra, 1999). In these studies, tumour adhesion appeared to precede dissagregation of the mesothelial monolayer, and could be partially blocked by pretreatment with anti-CD44 and anti-b1 antibodies.…”
mentioning
confidence: 91%
“…Modulation of cell-cell and cell-matrix adhesion are key events in ovarian cancer metastasis, as intraperitoneal adhesion of malignant cells and multicellular aggregates combined with localized integrin-mediated invasion of the collagen-rich submesothelial matrix are necessary to anchor secondary lesions (5,40). Intraperitoneal ovarian cancer metastasis is mediated by adhesion via integrins ␣2␤1 and ␣3␤1 to peritoneal mesothelial cells displaying surface expression of collagen and the exposed interstitial (types I and III) collagen-rich submesothelial matrix, and antibodies directed against these integrins block collagen binding (41)(42)(43)(44)(45)(46)(47). Integrin engagement by a multivalent matrix ligand results in receptor aggregation, functionally coupling the extracellular environment to specific signal transduction pathways that modulate distinct cellular responses, including gene transcription, cell migration, and survival (48).…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian carcinoma, integrins have been shown to mediate the organisation of extracellular matrix (ECM) (Carreiras et al, 1999a), adhesion to ECM components (Lessan et al, 1999) and cell motility (Carreiras et al, 1999b). The b1 family of integrins and CD44 has been shown to mediate interactions between ovarian carcinoma cells and the mesothelial cells that line the abdominal organs (Lessan et al, 1999). CD44 binds the ECM glycosaminoglycan hyaluronan with high affinity (Casey and Skubitz, 2000) and affects cell adhesion (Lessan et al, 1999), migration (Casey and Skubitz, 2000) and tumour growth (Strobel et al, 1997) in ovarian carcinoma cells.…”
mentioning
confidence: 99%
“…The b1 family of integrins and CD44 has been shown to mediate interactions between ovarian carcinoma cells and the mesothelial cells that line the abdominal organs (Lessan et al, 1999). CD44 binds the ECM glycosaminoglycan hyaluronan with high affinity (Casey and Skubitz, 2000) and affects cell adhesion (Lessan et al, 1999), migration (Casey and Skubitz, 2000) and tumour growth (Strobel et al, 1997) in ovarian carcinoma cells.…”
mentioning
confidence: 99%